Silver-copper composite strip for automobile fuse and preparation method of silver-copper composite strip

By using silver-copper composite strips in the fuse materials and setting up a transition layer of silver-copper alloy therebetween, the existing fuse materials have been solved in terms of mechanical strength, cost, corrosion resistance and fuse response speed, and the improvement of current shock resistance, rapid fuse and shock resistance are achieved, and the production process is simplified and the cost is reduced.

CN119626866APending Publication Date: 2025-03-14CHONGQING CHUANYI AUTOMATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411784532.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing fuse materials such as sterling silver and pure copper have problems such as low mechanical strength, high cost, poor corrosion resistance and slow fuse response in applications, which are difficult to meet the high performance requirements of fuse materials in new energy vehicles.

Method used

A silver-copper composite strip is used, and a silver-copper alloy transition layer is arranged between silver and copper, with a thickness of 1.0 to 3.0 μm. The preparation method includes continuous in-line groove, annealing, diffusion annealing and rolling, forming a transition layer with uniform thickness and controllable thickness to achieve smooth transition of electrothermal properties and the firmness of metallurgical bonding.

Benefits of technology

It has achieved resistance to instantaneous high current impact, rapid fuse response and good earthquake resistance, which significantly improved the comprehensive service performance of composite strips. It also has a high degree of automation in the preparation method, simple and stable processing process, and is easy to produce in a large batch continuously, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626866A_ABST
    Figure CN119626866A_ABST
Patent Text Reader

Abstract

The invention discloses a silver-copper composite strip for an automobile fuse and a preparation method of the silver-copper composite strip, the silver-copper composite strip is formed by arranging silver and copper alternately, a silver-copper alloy transition layer is arranged between the silver and the copper, and the thickness of the silver-copper alloy transition layer is 1.0-3.0 microns. A silver-copper alloy transition layer with uniform and controllable thickness is formed through thermal diffusion, so that smooth transition and firm metallurgical bonding of electrothermal properties among layers are realized, and the comprehensive service performance of the composite strip is remarkably improved; and secondly, the preparation method is high in automation degree, the processing process is simple and stable, large-batch continuous production is easy to realize, the production cost is reduced, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal processing, and in particular to a silver-copper composite strip for an automobile fuse and a preparation method thereof. Background Art

[0002] As a key component of circuit protection, fuses are widely used in power systems, industrial equipment and household appliances. Their core function is to quickly blow when the circuit is overloaded or short-circuited to protect the safety of circuits and electrical equipment. Although traditional fuse materials such as pure silver and pure copper have their own advantages, they all have obvious limitations. Pure silver is widely used in the field of fuses due to its high conductivity, low melting point and good corrosion resistance, but its low mechanical strength and high cost have become its application bottleneck. Pure copper has the advantages of high mechanical strength and low cost, but its corrosion resistance is poor and the fusing response speed is slow, which limits its application in some high-demand occasions.

[0003] Silver-copper composite strips combine the advantages of pure silver and pure copper. Through reasonable material composite design, excellent performance fuse materials can be produced. In order to overcome the limitations of a single material, silver-copper composite strips came into being. However, there are many problems with the existing preparation methods.

[0004] For example, the Chinese patent with publication number CN101281839A discloses a method of sintering and compounding by adding silver-copper alloy brazing material between silver bars and copper bars. Although this method can achieve silver-copper compounding, the electrothermal properties of the thicker alloy brazing material at the joint are different from those of pure copper and pure silver. The melting point of the brazing alloy material is lower than that of pure copper and pure silver, and the resistivity is higher than that of pure copper and pure silver. Local overheating and current disorder may occur, leading to premature failure. In addition, this method is limited by the length of the blank and the clamping mold, making it difficult to achieve continuous mass production.

[0005] For another example, the Chinese patent with publication number CN104416004A discloses a method for making a through-structure composite strip, which is to make a through-structure silver-copper composite strip by grooving the front and back sides of a copper bar or copper strip and performing two composite processes. However, the strip produced by this method lacks a transition layer between the copper layer and the silver layer, and no effective metallurgical bonding is formed, resulting in poor composite strength and difficulty in meeting long-term high-frequency vibration conditions. At the same time, this method has redundant processes, low level of automated processing, and is not conducive to mass production.

[0006] With the rapid development of new energy vehicles, higher requirements are placed on the performance of fuse materials, such as resistance to instantaneous large current shocks, fast fuse response, and good seismic resistance.

[0007] Therefore, those skilled in the art are committed to developing a silver-copper composite strip for automotive fuses that is resistant to instantaneous large current impacts, has a fast fuse response, has good shock resistance, and is easy to mass produce, and a preparation method thereof. Summary of the invention

[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide a silver-copper composite strip for automotive fuses that is resistant to instantaneous large current impacts, has a fast fuse response, has good seismic resistance, and is easy to mass produce, and a preparation method thereof.

[0009] To achieve the aforementioned object of the invention, the present invention provides a silver-copper composite strip for automotive fuses, which is composed of silver and copper arranged alternately, a silver-copper alloy transition layer is provided between the silver and copper, and the thickness of the silver-copper alloy transition layer is 1.0 to 3.0 μm.

[0010] The present invention also provides a method for preparing the above-mentioned silver-copper composite strip for automobile fuse, comprising the following steps:

[0011] (1) Preparation of composite semi-billets: The front side of the copper base strip is continuously grooved online to clean the metal surface; then the silver wire is evenly inserted into the groove of the copper strip to form a composite semi-billet;

[0012] (2) Annealing: annealing the composite semi-blank;

[0013] (3) preparing a composite blank: performing a second continuous slotting on the back of the annealed copper base strip, wherein the slotting position is located on the back of the aforementioned slotting, and the metal surface is cleaned; then silver wires are uniformly inserted into the grooves of the copper strip to obtain a composite blank;

[0014] (4) Packing heat treatment: The composite blank is subjected to diffusion annealing treatment, the diffusion annealing temperature is 300°C to 400°C, the annealing time is 120 to 270 minutes, and it is carried out under a protective atmosphere;

[0015] (5) Rolling: rolling the annealed composite billet to the required finished product thickness specification;

[0016] (6) Slitting: Slitting the rolled billet into strips to the finished product width specifications.

[0017] Furthermore, in step (4), the protective atmosphere is one of nitrogen, hydrogen, ammonia decomposition gas, argon and carbon monoxide gas.

[0018] Furthermore, in step (1), the groove depth is 1 / 2 of the thickness of the copper base strip.

[0019] Furthermore, in step (4), the diffusion annealing time is 240 to 270 minutes.

[0020] Compared with the prior art, the advantages of the present invention are that the transition layer with uniform and controllable thickness is formed by thermal diffusion, which realizes the smooth transition of the electrothermal properties between the layers and the firmness of the metallurgical bonding, has the characteristics of resistance to instantaneous large current shocks, fast fuse response and good seismic resistance, and significantly improves the comprehensive service performance of the composite strip; secondly, the preparation method of the present invention has a high degree of automation, a streamlined and stable processing process, and is easy to realize large-scale continuous production, which reduces production costs and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the structure of the silver-copper composite strip of the present invention;

[0022] Figure 2 This is a result diagram of the bonding strength test of the silver-copper composite strip of the present invention;

[0023] Figure 3 This is the phase diagram of Ag-Cu binary alloy. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present application, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used herein have the common meanings understood by those skilled in the art for the present application. In case of conflict, the definitions in this specification shall prevail.

[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present application in any way, that is, the content of the present application can be implemented without being limited by any specific theory or mechanism.

[0026] As used herein, "this application" means "the present invention" or "the present disclosure".

[0027] The use of "one", "an", "a kind" or similar expressions to describe the components and technical features described in this application is merely for the convenience of expression and to provide a general meaning to the scope of this application. Therefore, such description should be understood to include one or at least one, and the singular also includes the plural, unless it is obvious that it refers to another meaning.

[0028] In this document, "or its combination" means "or any combination thereof", and "any one", "any one" means "any one", "any one" or "any one".

[0029] As used herein, the terms "comprises," "including," "having," "containing," or any other similar terms are open-ended transitional phrases that are intended to cover non-exclusive inclusions. For example, a composition or article containing multiple elements is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless otherwise expressly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or." For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, in this article, the terms "comprising", "including", "having", and "containing" should be interpreted as being specifically disclosed and simultaneously covering closed conjunctions such as "consisting of", "consisting of", and "the remainder is", as well as conjunctions such as "consisting essentially of", "mainly consisting of", "mainly consisting of", "basically containing", "essentially consisting of", "essentially consisting of", and "essentially containing".

[0030] In this article, all features or conditions such as numerical values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions), especially integer values. For example, the range description of "1.0 to 8.0" or "between 1.0 and 8.0" or "between 1.0 and 8.0" should be deemed to have specifically disclosed all sub-ranges such as 1.0 to 8.0, 1.0 to 7.0, 2.0 to 8.0, 2.0 to 6.0, 3.0 to 6.0, 4.0 to 8.0, 3.0 to 8.0, etc., and should be deemed to cover endpoint values, especially sub-ranges defined by integer values, and should be deemed to have specifically disclosed individual values ​​such as 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, etc. Unless otherwise indicated, the foregoing method of interpretation applies to all contents of the entire application, regardless of whether the scope is broad or not.

[0031] If the quantity, concentration or other numerical value or parameter is expressed as a range, a preferred range (or a better range) or a series of upper and lower limits, it should be understood that all ranges consisting of any pair of the upper limit or preferred value (or a better value) of the range and the lower limit or preferred value (or a better value) of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.

[0032] In this document, numerical values ​​should be understood to have the accuracy of the number of significant digits of the numerical value, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range of 39.50 to 40.49.

[0033] It should be understood that the features disclosed in the various embodiments herein may be arbitrarily combined to form the technical solution of the present application, as long as there is no contradiction in the combination of these features.

[0034] The present application will be described below with specific implementations and examples. It should be understood that these specific implementations and examples are merely illustrative and are not intended to limit the scope of the present application and its use.

[0035] Unless otherwise stated, the methods, reagents and conditions used in the following preparation examples, comparative examples and examples are conventional methods, reagents and conditions in the art.

[0036] Example 1

[0037] A method for preparing the above-mentioned silver-copper composite strip for automobile fuses comprises the following steps:

[0038] (1) Preparation of composite semi-billet: The front side of the copper base strip 1 is continuously grooved online, the groove depth is 1 / 2 of the thickness of the copper base strip, and the metal surface is cleaned; then the silver wire 2 is evenly inserted into the groove of the copper strip to form a composite semi-billet;

[0039] (2) Annealing: annealing the composite semi-blank;

[0040] (3) preparing a composite blank: performing a second continuous slotting on the back of the annealed copper base strip, wherein the slotting position is located on the back of the aforementioned slotting, and the metal surface is cleaned; then silver wires are uniformly inserted into the grooves of the copper strip to obtain a composite blank;

[0041] (4) Packing heat treatment: The composite blank is subjected to diffusion annealing treatment at a temperature of 300°C for 120 min under nitrogen;

[0042] (5) Rolling: rolling the annealed composite billet to the required finished product thickness specification of 0.2 mm;

[0043] (6) Slitting: Cut the rolled billet into strips with a finished width of 90 mm.

[0044] Finally, the formation Figure 1 The silver-copper composite strip shown, wherein 1 is a copper base strip, 2 is a silver wire, and 3 is a silver-copper alloy transition layer.

[0045] Examples 2 to 12 are obtained by changing the diffusion annealing temperature and annealing time on the basis of Example 1. Comparative Examples 1 to 3 are obtained by using the method used in patent CN104416004A. The length of the above comparative examples and examples is 300 mm.

[0046] The tensile strength test was carried out using a tensile testing machine. The test standard is GB-T 228.1-2021 Metallic materials - Tensile tests - Part 1: Room temperature test method. The thickness, tensile strength and fracture position results are shown in the following table:

[0047]

[0048]

[0049] It can be seen from the above table that the silver-copper alloy transition layers of Examples 1 to 12 are relatively obvious, and the thickness is controlled within 1.0-3.0 μm; Figure 2 It can be seen that during the tensile test, the silver-copper alloy bonding interface (the part circled in red in the figure), that is, the silver-copper alloy transition layer, did not break, the structural strength was high, and the fracture was located in the middle of the silver surface (the silver-white part in the figure); while comparative examples 1 to 3 had no obvious silver-copper alloy transition layer, were easier to break during the tensile test, and the fracture was located at the silver-copper bonding interface.

[0050] As the annealing time increases, the silver-copper alloy transition layer also increases; in addition, when the treatment time is 240-270 minutes, the thickness is optimal and the bonding strength is good. At a temperature of 300-400°C, a silver-copper alloy transition layer can be formed, but it has no effect on the thickness and bonding strength.

[0051] Interface electrothermal performance evaluation

[0052] The resistivity test and melting point comparison were performed on Examples 3, 6, 8 and Comparative Examples 4 and 5, wherein Comparative Examples 4 and 5 were prepared by the method disclosed in Patent CN101281839A; since the thickness of the silver-copper alloy transition layer in the present invention is 1.0-3.0 μm, the main components of its interface are Ag99.99 and Cu99.9; while Comparative Examples 4 and 5 use AgCu brazing materials, the main components of its interface are AgCu28; the resistivity test was performed according to the resistivity test method of precision resistance alloys in GB-T 6146-2010, and the melting point was measured by the attached Figure 3 The Ag-Cu binary alloy phase diagram was determined, and the results are shown in the following table:

[0053]

[0054] It can be seen from the above table that there is a thicker soldering layer between silver and copper in comparative examples 4 and 5, and its resistivity is greater than 22μΩ·mm, while the resistivity of this embodiment is less than 18μΩ·mm. At the same time, since the melting points of comparative examples 4 and 5 are less than 800°C, they are prone to premature heating and fusing failure under extreme working conditions such as instantaneous large currents; while the melting point of this embodiment is greater than 900°C, so it is not easy to cause premature heating and fusing failure under extreme working conditions such as instantaneous large currents.

[0055] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, some simple deductions or substitutions can be made without departing from the concept of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be covered within the protection scope of the present invention.

Claims

1. A silver-copper composite strip for automobile fuses, wherein silver and copper are arranged alternately, and characterized in that: A silver-copper alloy transition layer which has been heat treated by boxing is arranged between the silver and the copper, and the thickness of the silver-copper alloy transition layer is 1.0-3.0 μm.

2. A method for preparing the silver-copper composite strip for automobile fuse according to claim 1, characterized in that: The following steps are involved: (1) Preparation of composite semi-billets: The front side of the copper base strip is continuously grooved online to clean the metal surface; then the silver wire is evenly inserted into the groove of the copper strip to form a composite semi-billet; (2) Annealing: annealing the composite semi-blank; (3) preparing a composite blank: performing a second continuous slotting on the back of the annealed copper base strip, wherein the slotting position is located on the back of the aforementioned slotting, and the metal surface is cleaned; then silver wires are uniformly inserted into the grooves of the copper strip to obtain a composite blank; (4) Packing heat treatment: The composite blank is subjected to diffusion annealing treatment, the diffusion annealing temperature is 300°C to 400°C, the annealing time is 120 to 270 minutes, and it is carried out under a protective atmosphere; (5) Rolling: rolling the annealed composite billet to the required finished product thickness specification; (6) Slitting: Slitting the rolled billet into strips to the finished product width specifications.

3. The method for preparing the silver-copper composite strip for automobile fuse according to claim 2, characterized in that: In step (4), the protective atmosphere is one of nitrogen, hydrogen, ammonia decomposition gas, argon and carbon monoxide gas.

4. The method for preparing the silver-copper composite strip for automobile fuse according to claim 2, characterized in that: The diffusion annealing time in step (4) is 240 to 270 minutes.

5. The method for preparing the silver-copper composite strip for automobile fuse according to claim 2, characterized in that: In step (1), the depth of the groove is 1 / 2 of the thickness of the copper base strip.

Citation Information

Patent Citations

  • Belt material for fused mass of fuse and manufacturing method thereof

    CN101281839A

  • Method for producing penetrative composite strip and penetrative composite strip produced by same

    CN104416004A